Peru : Technical Assistance Report-Proposals for the 2022 Tax Reform: Mining Sector Fiscal Regime, Capital Gains, and IGV on Digital Services. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2022)
In October 2021, the MEF asked Congress for the delegation of powers to legislate on tax matters with the aim of increasing tax collections and doing so by adding progressivity to the Peruvian tax system. The initiative being developed by the MEF contains (tentatively, to date) around 40 specific measures-some administrative, others related to tax policy-that the MEF hopes will, as a whole, generate additional revenue for the treasury. The tax collection impact of quite a few of the measures (including those pertaining to the mining sector) has not been estimated, whereas the measures for which there is a calculation are estimated to bring in a little over 1 percent of GDP in revenues. Given Peru's low level of tax collections, both relative to its own historical trends as well as those of other countries in the region, the amount expected to be collected with the proposed reform is modest. However, increasing tax collections by enhancing progressivity would appear to be the right approach.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Peru